From psoriasis to psoriatic arthritis: epidemiological insights from a retrospective cohort study of 74,046 patients - Huo, An-Ping; Liao, Pei-Lun; Leong, Pui-Ying; Wei, James Cheng-Chung (Frontiers in Medicine, 2024)
Introduction To verify our hypothesis that psoriatic arthritis (PsA) is mainly genetically predetermined and distinct from psoriasis (PsO), we use the TriNetX database to investigate whether intrinsic factors outweigh externals in PsA emergence in PsO patients. Methods We conducted three retrospective cohort studies utilizing information from the TriNetX network, whether (a) PsO patients with type 2 diabetes mellitus (DM) face an elevated risk of developing PsA compared to those without type 2 DM; (b) PsO patients who smoke face a higher risk of PsA; and (c) PsO patients with type 2 DM who smoke are more likely to develop PsA than those who do not smoke. Results PsO patients with type 2 DM exhibited an elevated risk of developing PsA [hazard ratio (HR), 1.11; 95% CI 1.03–1.20], with the combined outcome demonstrating a heightened HR of 1.31 (95% CI 1.25–1.37). PsO patients with a smoking history exhibited an elevated risk of developing PsA (HR, 1.11; 95% CI 1.06–1.17), with the combined outcome demonstrating a heightened HR of 1.28 (95% CI 1.24–1.33). PsO patients with type 2 DM and a history of smoking were not found to be associated with an increased risk of developing PsA (HR, 1.05; 95% CI 0.92–1.20). However, the combined result revealed a higher risk of 1.15 (95% CI 1.06). Discussion These findings suggested that intrinsic factors outweigh external factors in PsA emergence in PsO patients. Further studies may focus on genetic disparities between PsO and PsA as potential risk indicators rather than solely on phenotypic distinctions.